Does Principal Leadership Affect Teacher’s Performance? A Case of Junior High School Teachers in Tangerang - Sumiyani Sumiyani; Soleh Hidayat; Aceng Hasani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research investigates the principal leadership that might affect teachers' performance at the Junior High School level. Methods: This research used a quantitative method with the type of correlational study. The sample of this research was 145 Junior High School teachers from Tangerang City. The samples were selected based on the simple random sampling technique. The instruments of this research are teacher performance questionnaires and principal leadership. The data was analyzed quantitatively using a simple regression formula with the help of SPSS IBM version 25. Result: The result indicated that the principal's leadership positively affected Indonesian language teachers' performance at Junior High School in Tangerang City. The abilities of a qualified school principal develop teacher professionalism because the principal conducts his duties appropriately, the principal understands the needs of the teachers and teaching staff, and leads his teachers well so that the four teacher competencies will not only develop but will increase so that teacher’s professionalism will be realized. The quality of education will be improved. Novelty: This research studies further topics that show that the principal leadership might have different styles applied to teachers that will influence their performance at work.